Interface between Tourism and Rural Development in Panchmul, Nepal (Nepalese Journal of Development and Rural Studies, 2021)
This study explores interfaces between tourism and rural development outcomes (constructs) in Panchmul located in Aandhikhola rural municipality of Syangja District. A comprehensive researcher strategy has been applied in this study. The necessary information was collected from 21 participants selected purposively from tourism and rural development programs. This study found functional interfaces or two ways contributions between tourism and rural development outcomes. Similarly, tourism related activities are building social capital, developing rural infrastructures, maintaining community well-being, and conserving biodiversity which are learning platforms to the neighboring villagers and others people. Panchmul can be a model village for rural development if skillful local youths are mobilized in the activities of tourism development, promotional, and management. That’s why there must be transformative interfaces between constructs thus better to apply the strategic interface model developed from this study by the local development stakeholders.